THE MATHEMATICAL ARGUMENTATION ABILITY AND ADVERSITY QUOTIENT (AQ) OF PRE-SERVICE MATHEMATICS TEACHER - Wahyu Hidayat; Wahyudin Wahyudin; Sufyani Prabawanto (Journal on Mathematics Education, 2018)
The Mathematical argumentation has been studied before, but no research has a focus on mathematical argumentation and adversity quotient of the pre-service mathematics teacher. This study is experimental research that aims to know and examine in depth about the influence of AQ of pre-service mathematics teacher toward the achievement of mathematical argument ability. The population of this study is the pre-service mathematics teacher in Cimahi City, West Java, Indonesia; while the sample is 60 pre-service mathematics teachers selected purposively. The instruments of this study are tests and non-tests. They are based on the assessment of good characteristics towards students' mathematical argumentation abilities, while the non-test instrument is based on the assessment of good characteristics towards AQ. The results of this research show that: (1) AQ gives positive influence to the development of mathematical argumentation ability of pre-service mathematics teacher with the influence of 60.2%, while the rest of it (39.8%) is influenced by other factors outside AQ; (2) The ability of mathematical argumentation of pre-service mathematics teacher is more developed on AQ of Climber type; (3) Students with the Quitter AQ type still tend to have less ability of mathematical argumentation.